The Cardboard Kingdom. Roar of the beast - Sell, Chad; Alliger, Vid; Betancourt, Manuel, (Writer) (New York : Alfred A. Knopf, 2021)
It's nearly Halloween in The Cardboard Kingdom, and one thing is for sure: a mystery is afoot. Nate is positive he saw a monster in his backyard. It wasn't a shadow or a rustling tree. It wasn't his eyes playing a trick on him. It was a monster, plain and simple. But the trouble is, no one believes him. Even his stepbrother, Elijah, says he must have imagined it... Until it shows up over and over again in the kingdom. Always at night, always on the move. This monster is quick, and it's, well, super scary. Even Vijay the Beast is rattled by this menacing new creature. But what does the monster want? Why has it come to the kingdom? And what can the kids do about it?
5.0.
3-6.
HL160L
Keywords: Imagination -- Comic books, strips, etc -- Juvenile fiction; Costume -- Comic books, strips, etc -- Juvenile fiction; Monsters -- Comic books, strips, etc -- Juvenile fiction; Adventure stories; Imagination -- Fiction; Costume -- Fiction; Monsters -- Fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Action and adventure comics; Graphic novels; High-low fiction; Comics (Graphic works)